2011
DOI: 10.1371/journal.pone.0021018
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential and Challenges of Targeting Receptor Tyrosine Kinase ROR1 with Monoclonal Antibodies in B-Cell Malignancies

Abstract: BackgroundBased on its selective cell surface expression in chronic lymphocytic leukemia (CLL) and mantle cell lymphoma (MCL), receptor tyrosine kinase ROR1 has recently emerged as a promising target for therapeutic monoclonal antibodies (mAbs). To further assess the suitability of ROR1 for targeted therapy of CLL and MCL, a panel of mAbs was generated and its therapeutic utility was investigated.Methodology and Principal FindingsA chimeric rabbit/human Fab library was generated from immunized rabbits and sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 45 publications
(76 reference statements)
4
90
1
1
Order By: Relevance
“…The identified functional epitopes of ROR1 in CLL will be further used in the development of human antibodies against ROR1 for clinical trials. The efficacy of our MAbs are in contrast to those produced by Yang et al 51 indicating that their MAbs might be more suitable as conjugates or chimeric antigen receptors. Their antibodies alone did not induce apoptosis, or mediated CDC and a low ADCC activity.…”
Section: Cd5contrasting
confidence: 60%
“…The identified functional epitopes of ROR1 in CLL will be further used in the development of human antibodies against ROR1 for clinical trials. The efficacy of our MAbs are in contrast to those produced by Yang et al 51 indicating that their MAbs might be more suitable as conjugates or chimeric antigen receptors. Their antibodies alone did not induce apoptosis, or mediated CDC and a low ADCC activity.…”
Section: Cd5contrasting
confidence: 60%
“…In a similar series of screens, we humanized a mouse (2A2) 28 and a rabbit (R11) 37 mAb specific for the cancer cell-associated surface marker ROR1. 30,37,38 Here, we used sets of humanized variable regions designed by grafting of CDRs into framework regions derived from a database of somatically hypermutated human sequences, and generated transposable libraries as described before.…”
Section: Transpo-mab Screening Of Humanized Anti-ror1 Antibody Librariesmentioning
confidence: 99%
“…30,37,38 Here, we used sets of humanized variable regions designed by grafting of CDRs into framework regions derived from a database of somatically hypermutated human sequences, and generated transposable libraries as described before. The humanized libraries consisted of 64 VH £ 49 VL and 101 VH £ 82 VL for 2A2 and R11, respectively ( Fig.…”
Section: Transpo-mab Screening Of Humanized Anti-ror1 Antibody Librariesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, all drugs currently on the market or in clinical trials are general immunosuppressants that fail to distinguish the pathogenic CLL cells from healthy B-cells. Ideally, drug targets would be identified that allow selective suppression or killing of the malignant CLL cells without interfering with the normal function of the humoral immune system (5).…”
Section: Chronic Lymphocytic Leukemia (Cll)mentioning
confidence: 99%